PENILAIAN LOWER URINARY TRACT SYMPTOMS (LUTS) PADA PENDERITA DIABETES MELITUS DI KOTA TEGAL - Khasanah, Dwi Uswatun; Suparjo, Suparjo; Fauziyah, Anny (Prodi Keperawatan Tegal Program Diploma III Poltekkes Kemenkes Semarang, 2025)
Diabetes Mellitus (DM) was associated with urological complications, particularly Lower Urinary Tract Symptoms (LUTS). LUTS included nocturia, urgency, frequency, decreased urine flow, incomplete bladder emptying, and incontinence, which could cause physical and psychological distress and reduce quality of life. Early identification of LUTS in patients with DM was essential to prevent progression and improve symptom management. This descriptive study aimed to identify LUTS in DM patients in Tegal City. A total of 106 respondents with DM were selected through purposive sampling from the service areas of Tegal Timur, Bandung, Debong Lor, and Margadana public health centers. Data were collected through interviews using the LURN Symptom Index-29 (LURN SI-29). Descriptive statistics were applied to analyze mean, standard deviation, minimum, and maximum values. The findings revealed that the highest mean score was in Section E (Nocturia) with 65.89 (SD = 22.16), followed by Section D (Urgency) with 22.42 (SD = 22.66). The lowest score was in Section B (Bladder Pain), with 7.02 (SD = 14.19). The total LURN SI-29 score had a mean of 19.15 (SD = 9.98), ranging from 5.70 to 53.30. In conclusion, nocturia was the most dominant symptom experienced by DM patientsin Tegal City, followed by urgency. Meanwhile, bladder pain was relatively rarely reported. Overall, the total LUTS score indicated that most DM patients experienced lower urinary tract symptoms with varying levels of severity. Early detection of LUTS was recommended to help DM patients recognize symptoms earlier and receive appropriate interventions.